EMERGING STRONGER: A TRANSCENDENTAL PHENOMENOLOGY ON FINANCIAL MANAGEMENT AMONG WIDOWS - Morada, Rhody Laynn; Robles, DJ Kim; Visto, Princess (12th International Scholars Conference 2025, 2026)
The experience of widowhood represents a profound personal and financial transition, often marked by the sudden responsibility of managing household finances independently. This study seeks to illuminate the lived experiences of widows as they confront and transcend the complexities of financial management after loss. This study on based on Bucket Theory of Financial Management, Social Support Theory and Rational Choice Theory. Utilizing a phenomenological approach, data was gathered through semi-structured interviews with eight widows to explore their lived experiences. The analysis, guided by Moustakas' phenomenological data analysis procedures. The setting of the study is located at the Southern Philippines. Purposive sampling was used and the data was gathered through in-depth interviews and documents analysis. The study reveals that widows often face profound challenges in managing finances, primarily due to their unpreparedness for the financial responsibilities that come with widowhood. The emotional and psychological impact of losing a spouse significantly compounds their struggle, revealing a critical gap in readiness for financial management and adaptation to change. Widows are frequently overwhelmed by grief, which affects their ability to effectively handle financial matters and plan for the future. Addressing the issue of unpreparedness is essential to improving the overall support structure for widows. By focusing on enhancing financial education and providing proactive assistance, it is possible to mitigate some of the challenges faced and foster a more supportive environment that facilitates smoother transitions and better outcomes for those in need. For further studies, it is recommended to conduct a case study on the strategies used by widows in their financial management.